On draft of intergovernmental agreement for development and use of reference materials of composition and properties of substances and materials - E. V. Osintseva (Стандартные образцы, 2017)
The article deals with information of development of a draft of Agreement for development and use of reference materials of composition and properties of substances and materials which was developed within Interstate Council for Standardization, Metrology and Certification